Central Europe as a regional security (sub)complex in the interwar period - ALEXANDRESCU, Mihai (Studia Universitatis Babeș-Bolyai Historia, 2022)
This article proposes the use of a tool for analyzing the evolution of the balance of power in interwar Central Europe, taking over the theory of the regional security complex formulated by the Copenhagen School. This study starts from the premise that in from 1921 to 1938, it can be affirmed that the ephemeral existence of a central European security complex was distinct from the classical security complex of Europe. Next, the analysis criteria specific to the regional security complex and the diplomatic developments that created the Central European security complex are presented. Article history: Received: 25.06.2022; Revised: 12.08.2022; Accepted: 12.08.2022; Available online: 15.09.2022 Rezumat: Acest articol propune utilizarea unui instrument de analiză a evoluției echilibrului de putere în Europa Centrală interbelică, preluând teoria complexului regional de securitate formulată de Şcoala de la Copenhaga. Acest studiu pleacă de la premisa că în perioada 1921-1938 se poate afirma existența efemeră a unui complex de securitate central european distinct de complexul clasic de securitate al Europei. In continuare, sunt prezentate criteriile de analiză specifice complexului regional de securitate şi evoluțiile diplomatice care au creionat complexul Central European de securitate. Cuvinte cheie: Europa Centrală echilibrul interbelic de putere, complex regional de securitate, alianțe regionale, Acordurile de la Locarno.